2005
DOI: 10.1002/pmic.200401028
|View full text |Cite
|
Sign up to set email alerts
|

Discovering high mobility group A molecular partners in tumour cells

Abstract: DNA-based activities rely on an extremely coordinated sequence of events performed by several chromatin-associated proteins which act in concert. High Mobility Group A (HMGA) proteins are non-histone architectural nuclear factors that participate in the regulation of specific genes but they are also believed to have a more general role in chromatin dynamics. The peculiarity of these proteins is their flexibility, both in terms of DNA-binding and in protein-protein interactions. Since these proteins act as core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 73 publications
2
73
0
Order By: Relevance
“…One microgram of each of the HMGA1 recombinant proteins was separated by SDS-PAGE and transferred to polyvinylidene difluoride membrane. Far Westerns were then carried out as previously described (36).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One microgram of each of the HMGA1 recombinant proteins was separated by SDS-PAGE and transferred to polyvinylidene difluoride membrane. Far Westerns were then carried out as previously described (36).…”
Section: Methodsmentioning
confidence: 99%
“…Because HMGA proteins have been shown to associate with and modulate the activity of several nuclear factors (1,2,36), here, we have explored whether HMGA may also influence the function of p53 family members. We found that HMGA1 associates in vivo with p53 family members, and that this interaction results in the inhibition of their tumor suppressor activity in thyroid cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that the ability of HMGA to participate in several type of processes is conferred by their interaction with a wide range of partners, including transcription factors, components of the splicing machinery, proteins involved in replication and chromatin assembly factors [26].…”
Section: Hmga Proteinsmentioning
confidence: 99%
“…Decreased NSC proliferation in the adult SVZ with age may thus be due, in part, to the observed decrease in the expression of Hmga2 in freshly isolated SVZ cells, which are enriched in neural stem and progenitors (Nishino et al, 2008). Although the role of HMGA2 in modulating chromatin structure in adult stem cells has not yet been addressed, studies in human fibroblasts suggest that HMGA2 alters chromatin compaction (Narita et al, 2006) or may complex with other structural chromatin-associated proteins (Sgarra et al, 2005(Sgarra et al, , 2008. Likely, decreasing levels of Hmga2 during aging (Nishino et al, 2008) results in altered chromatin compaction that either silences key stem cell proliferation genes or inappropriately activates genes, such p16 INK4a /p19 ARF , that limit stem cell function.…”
Section: Chromatin Structure In Adult Stem Cellsmentioning
confidence: 99%